Radiation Improvement of Low-Profile Microstrip Antenna by Utilizing AMC Surface for MIMO and Wireless Systems - Hosein Malekpoor; Mehdi Hamidkhani (International Journal of Industrial Electronics, Control and Optimization)
A compact microstrip antenna by applying a parasitic artificial magnetic conductor (AMC), is proposed for facilitating 4G and 5G wireless communications. The antenna design includes microstrip dipoles fed by a T-shaped feedline. Notably, the antenna achieves a measured bandwidth of 5.32-6.73 GHz (with S11≤ -10 dB). To enhance performance, a proposed parasitic AMC reflector is integrated into the antenna structure. Incorporating an 8×8 AMC array, the antenna extends its -10 dB measured bandwidth from 4.55 to 6.83 GHz, catering to both 4G and 5G communication standards. Comparative analysis with an antenna lacking AMC reveals a reduced size of 34%, alongside a notable gain of 8 dBi and uni-directional radiation patterns. The efficiency and gain of all elements are approximately 90% and 8 dBi, respectively. Moreover, the introduction of an AMC unit cell, well-founded on a parasitic patch, resonates at 6.12 GHz with a bandwidth extending from 5.25 to 7.15 GHz. Furthermore, the offered equivalent transmission line model of the antenna with the AMC is demonstrated, yielding desirable results. This model accurately predicts the input impedance of the antenna with AMC across a broad frequency band ranging from 4.61 to 6.72 GHz. This comprehensive study demonstrates the effectiveness and versatility of the offered model in characterizing the operating band's behavior of the antenna across a wide frequency band to facilitate its design and optimization for various applications.